Silica-PEG hybrid ormolytes: structure and properties - Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Da Silva, M.; Ribeiro, Clovis Augusto [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Elsevier B.V., 1999)
The effect of lithium salt doping on the structure and ionic conduction properties of silica-polyethyleneglycol composites is reported. These materials, so called ormolytes (organically modified electrolytes), were obtained by the sol-gel process. They have chemical stability due to the covalent bonds between the inorganic (silica) and organic (polymer) phase. The structure of these hybrid materials was investigated by small-angle X-ray scattering (SAXS) as a function of lithium concentration [O]/[Li] (O being the oxygens of the ether type). The spectra have a well-defined peak attributed to the existence of a liquid-like spatial correlation of silica clusters. The ionic conductivity was studied by AC impedance spectroscopy and is maximum for [O]/[Li] = 15. This result is consistent with SAXS and thermo-mechanical analysis measurements and is due to the formation of cross-linking between the polymer chains for the larger lithium concentrations. These materials are solid, transparent, flexible and have an ionic conductivity up to 10(-4) S/cm. (C) 1999 Elsevier B.V. B.V. All rights reserved.